DOES DIGITALIZATION MODERATE THE EFFECT OF INTERNAL FACTORS ON CONVENTIONAL BANK STABILITY? EVIDENCE FROM INDONESIA - Rifki Azis Syahrizal; Entot Suhartono; Zaky Machmuddah; Arditya Dian Andika (JAT : Journal Of Accounting and Tax, 2026)
Examination of the moderating function is the objective of this investigation of banking digitalization in addition to examining the effects of the Cost-to-Income Ratio, Loan Loss Provision to Total Loans, Bank Size, and Liquidity Ratio on banking stability. Although previous research has extensively investigated the impact of digitalization on banking stability, empirical findings regarding its function as a moderator in the relationship between banks' internal determinants and banking stability are still scarce, particularly for the conventional commercial institutions in developing countries such as Indonesia. Whether the effects of banks' internal determinants on banking stability are strengthened or weakened by banking digitalization is the focus of this study. During the 2020–2025 period, this study analyzed panel data from 47 conventional commercial banks listed on the Indonesia Stock Exchange using a quantitative approach, resulting in 282 observations. The Z-Score is employed as a metric for banking stability, while the IT Cost Ratio is employed to assess digitalization. Using a Moderated Regression Analysis approach, the data are analyzed using panel data regression. According to the findings, the Cost-to-Income Ratio and Bank Size have a significant and adverse impact on banking stability, whereas the Liquidity Ratio and Loan Loss Provision to Total Loans have a positive and significant impact. The Liquidity Ratio's beneficial impact on banking stability is further bolstered by the digitalization of banking.